They Say The Way To A Person's Heart Is Through Good Food. Can A Customer-Dominant Logic Enhance Customer Experience?: Evidence From The Restaurant Industry - Mehta, Disha (2014)
Marketing theory has evolved over the years from goods to service and now customer dominant logic. This shift in perspective has given rise to the need to study customer experience and value co-creation from the customer’s perspective, by launching and enquiry into their life-world. This research contextualises customer-dominant logic theory to explore whether such an approach can influence a customer’s experience of a service. An Interpretivist and phenomenological approach is undertaken to understand consumers’ life world context and their experiences of the past, along with expectations from the service in the future. The findings concur that c-d logic does influence customer experience. Managerial implications are discussed to suggest recommendations to managers on how to improve their overall business performance, without losing sight of their primary goal, that is, delivering high value meal experiences.